Experiences of children and young people from ethnic minorities in accessing mental health care and support: rapid scoping review - Helen Coelho; Anna Price; Fraizer Kiff; Laura Trigg; Sophie Robinson; Jo Thompson Coon; Rob Anderson (NIHR Journals Library, 2022)
Background: Mental health problems are common among children and young people in the UK. Some young people from ethnic minority backgrounds experience mental health problems in different ways from those from non-ethnic minority backgrounds. Furthermore, those from ethnic minority backgrounds often experience greater difficulties in accessing mental health support and variable levels of engagement with services, and may prefer different support to their white British peers. Objective: To describe the nature and scope of qualitative research about the experiences of children and young people from ethnic minority backgrounds in seeking or obtaining care or support for mental health problems. Data sources: We searched seven bibliographic databases (Applied Social Sciences Index and Abstracts, Cumulative Index to Nursing and Allied Health Literature, MEDLINE, PsycInfo®, Health Management Information Consortium, Social Policy and Practice, and Web of Science) using relevant terms on 23 June 2021. Methods: The scoping review included qualitative research about young people's experiences of seeking or engaging with services or support for mental health problems. Included studies were published from 2012 onwards, were from the UK, were about those aged 10-24 years and were focused on those from ethnic minority backgrounds (i.e. not white British). Study selection, data extraction and quality assessment (with 'Wallace' criteria) were conducted by two reviewers. We provide a descriptive summary of the aims, scope, sample, methods and quality of the included studies, and a selected presentation of authors' findings (i.e. no formal synthesis). Results: From 5335 unique search records, we included 26 papers or reports describing 22 diverse qualitative studies. Most of the studies were well conducted and clearly described. There were studies of refugees/asylum seekers (n = 5), university students (n = 4) and studies among young people experiencing particular mental health problems (n = 14) (some studies appear in multiple categories): schizophrenia or psychosis (n = 3), eating disorders (n = 3), post-traumatic stress disorder (n = 3, in asylum seekers), substance misuse (n = 2), self-harm (n = 2) and obsessive-compulsive disorder (n = 1). There were also three studies of ethnic minority young people who were receiving particular treatments (cognitive-behavioural therapy, multisystemic therapy for families and a culturally adapted family-based talking therapy). Most studies had been conducted with young people or their parents from a range of different ethnic backgrounds. However, nine studies were conducted with particular ethnic groups: asylum seekers from Afghanistan (n = 2), and black and South Asian (n = 2), black African and black Caribbean (n = 2), South Asian (n = 1), Pakistani or Bangladeshi (n = 1) and Orthodox Jewish (n = 1) people. The studies suggested a range of factors that influence care-seeking and access to mental health care, in terms of the beliefs and knowledge of young people and their parents, the design and promotion of services, and the characteristics of care professionals. Poor access was attributed to a lack of understanding of mental health problems, lack of information about services, lack of trust in care professionals, social stigma and cultural expectations about mental resilience. Limitations: As this was a rapid scoping review, there was only a basic synthesis of the research findings. Future work: Future research about young people from ethnic minorities could cover a wider range of ethnic minorities, sample and analyse experiences from particular ethnic minorities separately, cover those accessing different services for different needs, and adopt multiple perspectives (e.g. service user, carer, clinician, service management). Study registration: This study is registered as https://osf.io/wa7bf/. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery programme and will be published in full in Health and Social Care Delivery; Vol. 10, No. 22. See the NIHR Journals Library website for further project information.